Analisis Perlindungan Hukum Konsumen Terhadap Perjanjian Pembiayaan Pada Perseroan Terbatas Bintang Mas Dalam Pembayaran Pajak Kendaraan Bermotor - Pratiwi, Marlia; Santina, Rika; Maulidiana, Lina (VIVA THEMIS, 2025)
This research aims to analyze consumer legal protection for financing agreements at PT. Bintang Mas. This research is a type of field research using a qualitative approach, where this research directly observes and participates in related objects, namely taxpayers who make payments at the Samsat UPTD I Bandar Lampung office. Based on the results of the analysis, it was concluded that there was a default committed by the financing company, which in this case was PT. Bintang Mas Bandar Lampung has closed its office activities and none of the directors can be found and held accountable, resulting in huge losses for consumers, consumers have finished carrying out their responsibilities but the finance company is free from responsibility and has no good intentions to complete it. these problems, consumers of PT. Bintang Mas is the victim of a breach of contract committed by the finance company, having difficulty in paying taxes because Samsat UPTD 1 Bandar Lampung requires taxpayers to be able to include original Proof of Motor Vehicle Ownership (BPKB)